Global warming and acid atmospheric deposition impacts on carbonate dissolution and CO2 fluxes in French karst hydrosystems: Evidence from hydrochemical monitoring in recent decades. (1st February 2020) - Binet, S.; Probst, J.L.; Batiot, C.; Seidel, J.L.; Emblanch, C.; Peyraube, N.; Charlier, J.-B.; Bakalowicz, M.; Probst, A.
Abstract: The long-term change in surface water chemistry over time in remote areas is usually related to global change, including several processes such as global warming and acid atmospheric pollution. These cumulative factors limit the quantitative interpretation of the global warming effect on surface water acidification in relation to the atmospheric CO2 sink. To quantitatively estimate the impact of global warming on the atmospheric/soil CO2 uptake by carbonate weathering, the approach proposed here involves discriminating the proportion of [Ca + Mg] in waters resulting from soil carbonic acid dissolution (equal to the amount of CO2 uptake from soil/atmosphere) from the proportion resulting from strong acid pollution. This approach was applied to 5 karst hydrosystems located in France, far from local pollution sources and with several decades of hydrochemical monitoring. [Ca + Mg] from acid deposition represented between 16 and 25% of the total [Ca + Mg] concentration and the flux was positively correlated with the atmospheric deposition flux. This [Ca + Mg] increase is associated with increasing [Mg] and was found to be driven by the acid pollution inputs. Equilibrating water with calcite in presence of carbonic acid will release [Ca + Mg] into solution. The input of strong acids from atmospheric pollution contributes more to magnesian calcite dissolution because its solubility is lower than that of calcite. Since the 1980s, the decrease in [Ca + Mg] production due to the decrease in acid atmospheric deposition has minimized the increase in [Ca + Mg] linked to CO2 partial pressure (pCO2 ) increasing with global warming. It was found that [Ca + Mg] from H2 CO3 dissolution did not decrease with an increase in air temperature, as suggested by carbonate solubility. The annual fluxes of Ca + Mg from H2 CO3 dissolution, calculated for an average flow, showed a positive gradient with air temperature, of about 0.061 mol m 2 yr −1 °C −1 (±0.006). In low rainfall areas, the pCO2 increase with air temperature was stronger than in rainy areas. For an average specific discharge of 300 L m −2 yr −1, global warming is estimated to increase the CO2 uptake flux by about 204 micromol L −1 °C −1 (5.7% of the observed flux).